Attenuated SARS-CoV-2 variants with deletions at the S1/S2 junction - Siu-Ying Lau; Pui Wang; Bobo Wing-Yee Mok; Anna Jinxia Zhang; Hin Chu; Andrew Chak-Yiu Lee; Shaofeng Deng; Pin Chen; Kwok-Hung Chan; Wenjun Song; Zhiwei Chen; Kelvin Kai-Wang To; et al. (Emerging Microbes and Infections)
The emergence of SARS-CoV-2 has led to the current global coronavirus pandemic and more than one million infections since December 2019. The exact origin of SARS-CoV-2 remains elusive, but the presence of a distinct motif in the S1/S2 junction region suggests the possible acquisition of cleavage site(s) in the spike protein that promoted cross-species transmission. Through plaque purification of Vero-E6 cultured SARS-CoV-2, we found a series of variants which contain 15-30-bp deletions (Del-mut) or point mutations respectively at the S1/S2 junction. Examination of the original clinical specimen from which the isolate was derived, and 26 additional SARS-CoV-2 positive clinical specimens, failed to detect these variants. Infection of hamsters shows that one of the variants (Del-mut-1) which carries deletion of 10 amino acids (30bp) does not cause the body weight loss or more severe pathological changes in the lungs that is associated with wild type virus infection. We suggest that the unique cleavage motif promoting SARS-CoV-2 infection in humans may be under strong selective pressure, given that replication in permissive Vero-E6 cells leads to the loss of this adaptive function. It would be important to screen the prevalence of these variants in asymptomatic infected cases. The potential of the Del-mut variants as an attenuated vaccine or laboratory tool should be evaluated.